Dinamika enodimenzionalnih sistemov - Grubelnik , Vladimir; Marhl, Marko (University of Maribor Press, 2024)
Dynamics of One-Dimensional Systems. The textbook addresses one-dimensional dynamic systems with an elementary approach. The goal is to enable students to better understand the fundamental principles of system dynamics, such as identifying stationary states, stability analysis, bifurcations, and the long-term behavior of systems. The textbook is primarily designed for physics students, but it is also useful for other disciplines where mathematical modeling of dynamic systems is part of the curriculum. The content sections of the textbook cover the basic characteristics of dynamic systems, the geometric approach to solving one-dimensional systems, flows on a circle, bifurcations and their characteristics, one-dimensional mappings (maps), and numerous examples of one-dimensional systems in physics, biology, and chemistry. The examples are selected to help students develop intuition for the dynamics of more complex multi-dimensional systems they encounter in everyday life.